Validating a points-based effort expenditure for rewards task - Sturm, Emily T., author; Thomas, Michael L., advisor; Seger, Carol, committee member; Stephens, Jaclyn, committee member; Tompkins, Sara Anne, committee member (Colorado State University. Libraries, 2024)
Invalid performance on neurocognitive tests due to lack of effort expenditure is a concern for researchers and clinicians. Performance validity tests determine when adequate effort has been expended, but they fail to differentiate between subcomponents of effort that may be responsible for poor performance. The Effort Expenditure for Reward Task (EEfRT) is a task that provides separate measurements of reward processing and valuation constructs which could be informative as performance validity indicators. However, previous versions of the EEfRT use monetary performance-based rewards to investigate the expected value of effort, which can be problematic due to the influence of socio-economic factors and potential to systematically disadvantage participants with neurocognitive disorders. This study first aimed to examine the construct validity, specifically, the construct representation of a points-based version of the EEfRT online and in-person. The second aim of this study, which is exploratory, is to characterize patterns in embedded performance validity test performance obtained for separate neurocognitive measures as well as the EEfRT, thereby informing nomothetic span, or patterns of significant relations across measures of effort. This aim assessed whether the scores from the EEfRT indicate performance validity in other domains. Online participants (n = 342) from Prolific.com for the online sample and in-person participants (n = 27) were recruited via advertisements. Participants completed a battery including the EEfRT along with three working memory tasks, two executive functioning tasks, and one reward learning task. Results of regression analyses showed that, as hypothesized, both online and in-person participants chose hard tasks significantly more often at higher reward levels and at higher probability levels. However, contrary to expectations, a significant interaction between reward and group showed that points were more motivating in the online setting compared to in-person. Exploratory latent profile analysis revealed no clear pattern in embedded performance validity tests within the EEfRT or across other tasks. The results of this study suggest that a points-based version of the EEfRT is potentially valid for measuring effort-based decision making, but more research is needed before it can be called an objective measure of effort in the context of validating performance on cognitive tests.
Keywords: effort valuation; performance validity; effort; reward valuation; effort-based decision making